PYGMALION: A STUDY OF SOCIO-SEMANTICS - Mirjam Anugerahwati (TEFLIN, 2010)
Abstract: This article discusses the novel Pygmalion by George Bernard Shaw (1957) which depicts Eliza, a flower girl from East London, who became the subject of an âexperimentâ by a Professor of Phonetics who vowed to change the way she spoke. The story is an excellent example of a very real and contextual portrait ofÂ how language, particularly socio-semantics, play a role in the achievement of communicative competence.